Demographical and Socio-Economical Characteristics of Poor Households with Children in Postmodern Society - Кamelia Petkova (Проблеми на постмодерността, 2012)
In terms of economic and financial crisis, child poverty has emerged as an important issue for most European countries and Bulgaria. Given that children are dependent category is identifiable with the primary groups (family, household), they should be considered based on the specifics that these families, households have. In this article, based on a sociological analysis of data from international and national studies have outlined the main types of households who are at highest risk of living in poverty.